Chuntaivatral Chooranam (Polyherbal Formulation) in Siddha Medicine- A Literature Review (International Journal of Ayurveda and Pharma Research, 2025)
Chuntaivatral Chooranam is a polyherbal preparation which is used in the treatment of various diseases such as diarrhea, dysentery, indigestion, and haemorrhoids. This Chooranam is mentioned in Siddha Vaitya Thirattu and is prepared with 7 ingredients. This review study is focused to develop scientific documentary evidence for medicinal ingredients of Chuntaivatral Chooranam. This study presents an organized compilation and analysis of data sourced from traditional Siddha Medicine textbooks and research publications on website. The data drawn from variety of ancient and contemporary texts were systematically collected and categorized from Oct to Nov 2024. Collected data were processed and analyzed by using MS Excel spreadsheets. All ingredients of Chuntaivatral Chooranam are herbs, which are from 7 different families. According to the data, parts used in the plants are 7 different sources as dried fruit, leaf, dried pericarp, kernel, fruit rind, fruit, and seed; each of them represents 14.28%. Out of 7 ingredients 42.85% has astringent taste, 57.14% with cold potency and 85.71% with pungent efficacy. Based on phytochemical analysis among the ingredients; 100% of the ingredients constitute flavonoids, tannin, phenol, saponin, volatile oil, alkaloid, and ascorbic acid, while 42.85% of them are carbohydrates and protein (42.85%). All the ingredients show astringent, antimicrobial and antioxidant activity, 85.71% of them exhibit anti-diarrheal while 57.14% shows stomachic, anthelmintic and anti-diabetic activity each. Therefore, this review provides useful documentation of Chuntaivatral Chooranam. However further scientific studies should be performed in future regarding chemical and toxicity analysis.